The production of foot-and-mouth disease virus-like particles in the plant Nicotiana benthamiana: a potential candidate vaccine for foot-and-mouth disease - O'Connor, Steven Patrick (Department of Molecular and Cell Biology, 2019)
Foot and mouth disease virus (FMDV) infects cloven-hoofed animals causing the highly contagious foot and mouth disease. It is spread by contact or through aerosol. The disease is often debilitating for infected animals and can be fatal. Severe measures are taken to contain outbreaks; quarantine and trade restrictions are imposed and herds with infected individuals are culled to prevent the spread of the disease. Consequently, outbreaks of the disease have drastic implications for agriculture and social economies which can be devastating for affected countries. There are seven serotypes of the virus; of which SAT1, SAT2, and SAT3 are endemic to Africa. South African buffalo populations such as those in the Kruger National Park, are natural carriers of FMDV (Thomson 1995). Careful monitoring and regular vaccination are necessary to detect and prevent outbreaks and the spread of the disease to livestock of neighbouring areas and farms. The vaccines currently used are inactivated FMDV virions. These are produced in cell culture, an expensive process that requires high levels of biosafety. Furthermore, inactivated virions present non-structural proteins (NSPs) and thus cannot be distinguished from the infectious virus by imported ELISA kits that utilise the NSPs as coating antigens and conventionally produced detecting antibodies. We aimed to use recombinant constructs encoding the FMDV capsid and protease genes, cloned into the different vectors; pRIC, pEAQ and pTRAc, for transient expression in Nicotiana benthamiana to generate virus-like particles as an alternative vaccine candidate. Using a plant based expression system presents numerous advantages over the traditional cell culture production of the vaccine currently used. After having synthesised the FMDV genes P12A and 3C, the fusion gene P1-2A-3C (required for the vaccine) was cloned into these different plant expression vectors available in our laboratory. With Agrobacteria mediated infiltration of N. benthamiana, we demonstrated expression of recombinant protein by western blotting; and Coomassie stain, for each of the different constructs. Analytical ultra-centrifugation through a sucrose gradient was used to purify protein extracts. Comparison against a dilution series of bovine serum albumin was used to quantify the yield for each respective vector construct by densitometry. Transmission Electron Microscopy (TEM) imaging was used to qualitatively determine virus-like particle (VLP) assembly. In conclusion, we demonstrate proof of concept for a viable alternative approach for the production of a candidate vaccine for FMDV.